InAsSb on GaAs (001): influence of the arsenic molecules form on composition and crystalline properties of MBE layers. (October 2015) - Emel'yanov, E A; Vasev, A V; Semyagin, B R; Vasilenko, A P; Komanov, A A; Gutakovskii, A K; Putyato, M A; Preobrazhenskii, V V
Abstract: The influence of As molecular form on the composition and crystalline properties of InAsx Sb1-x solid solutions with MBE has been experimentally investigated. A series of samples has been grown at different growth temperatures. The grown samples were studied with the HRXRD and TEM methods. The incorporation coefficient of As4 and As2 molecules were determined at different growth temperatures. It has been found that the incorporation coefficient of As4 much more dependent on growth temperature compared to As2 . It has been found that at a low growth temperature a step-like increase of Sb fraction in an InAsx Sb1-x film leads to a decrease of threading dislocations density in a layer with a smaller x .